A Man for All Seasons: Fluidity of Perspective in Samuel Hearne’s Journey from Prince of Wales’s Fort in Hudson’s Bay to the Northern Ocean - Byrne, Paul Johnson (Studies in Canadian Literature, 2011)
More than two centuries have passed since a twenty-four-year-old Samuel Hearne first set out from the northernmost outpost of the Hudson’s Bay Company in search of what was then known as Rupert’s Land. Hearne’s 1795 documentation of his travels, Journey from Prince of Wale’s Fort in Hudson’s Bay to the Northern Ocean, reveals his dual – and at times duelling – perspective on his experiences. His impressions of the land and its inhabitants are shaped, on the one hand, by his attachment to the Hudson’s Bay Company as a dutiful servant of its economic interests, and, on the other, by his sense of himself as a traveller of impartial observation. It is in Hearne’s capacity for ironic detachment and the confluence of his shifting points of view that he often achieves a surprisingly balanced distance of remove from which he is able at once to perceive the intrinsic reasonableness of a foreign culture within its local context and to interrogate his own cultural knowledge and values.